EFEKTIVITAS PENGGUNAAN METODE CERAMAH BERVARIASI DALAM MENINGKATKAN OPERASI PERKALIAN BAGI ANAK BERKESULITAN BELAJAR - Resmi Novita (Universitas Negeri Padang, 2014)
Abstract: This research was derived from the problem faced by the students in the third grade of SDN 17 Jawa Gadut Padang in which they got problems to multiply numbers from 5 to 9. This was caused by the students who tended to memorize the numbers. The purpose of this research was to overcome the problem found in this research and to improve the students’ ability to multiply numbers from 5 to 9, and the students were expected to be able to memorize multiplication from 5 to 9. This was a quasi experimental research which used Pretest Posttest Design. Using this design, experiment was only done to a group without presenting the control group. The subject of the research was four students in the third grade of SDN 17 Jawa Gadut Padang. The data obtained was analyzed by using U Mann-Whitney test. The research hypothesis would be accepted if the value of Ucalculated > Utable on the significance level 95% or α = 0,05. The result of data analysis indicated that Ucalculated (0,5) was bigger than Utable (0) indicating that the hypothesis was accepted. Thus, the result of the research showed that applying various lecturing method through question and answer, assigning task, giving exercise and demonstrating the task by using multiple set was effective to improve the students with learning disabilities ability to multiply number from 5 to 9. Kata kunci : Multiple Set; Kemampuan Perkalian; Anak Berkesulitan Belajar